Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.7895/ijadr.v3i1.158
|View full text |Cite
|
Sign up to set email alerts
|

Women’s receptivity to Fetal Alcohol Spectrum Disorders prevention approaches: A case study of two regions in Russia

Abstract: Aims This study obtained data to inform the development of programs for prevention of Fetal Alcohol Spectrum Disorders (FASD) by examining Russian women’s perceptions about the determinants of their decisions regarding alcohol consumption during pregnancy; the importance of educating professionals and community about FASD; and the credibility of various sources of information. Design Cross-sectional survey. Setting Seven women’s clinics in St. Petersburg and the Nizhny Novgorod region in Russia. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Sending information materials to doctors and health professionals so that they can inform their patients Our findings are in line with the studies from Australia, Russia, the United States and the Netherlands, which showed that health professionals (including midwives, obstetricians, gynaecologists, and nurses) were among the most preferred and influential sources of information for pregnant and nonpregnant women of childbearing age in relation to alcohol use during pregnancy (9,(15)(16)(17). This aligns with the opinions of health professionals who feel that they should provide advice on alcohol use during pregnancy, although screening, providing correct advice, and interventions (where indicated) are often inadequate (18)(19)(20)(21).…”
Section: Strategy "Effective" or "Very Effective" N (%)supporting
confidence: 87%
“…Sending information materials to doctors and health professionals so that they can inform their patients Our findings are in line with the studies from Australia, Russia, the United States and the Netherlands, which showed that health professionals (including midwives, obstetricians, gynaecologists, and nurses) were among the most preferred and influential sources of information for pregnant and nonpregnant women of childbearing age in relation to alcohol use during pregnancy (9,(15)(16)(17). This aligns with the opinions of health professionals who feel that they should provide advice on alcohol use during pregnancy, although screening, providing correct advice, and interventions (where indicated) are often inadequate (18)(19)(20)(21).…”
Section: Strategy "Effective" or "Very Effective" N (%)supporting
confidence: 87%
“…In Russia, for example, Balachova and colleagues (2014) identified mothers’ and clinicians’ knowledge of FASD as important factors in a woman’s choice to drink during pregnancy. Younger women also valued the knowledge and opinions of husbands, mothers, friends, and coworkers, suggesting it is important to educate these individuals as well.…”
Section: Addressing Cultural Barriers To Implementationmentioning
confidence: 99%
“…Petrenko and colleagues (2014) and Balachova and colleagues (2014) have done important work toward understanding the unique perspectives of individuals within their communities. Ceccanti and colleagues (2007) conducted similar work in Italy in order to more fully understand the Italian phenotype of FASD and the drinking habits of Italian women for the purposes of better targeting mechanisms for prevention and intervention.…”
Section: Addressing Cultural Barriers To Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…When study location was crossed with women’s pregnancy status, the demographics differed significantly by group, except for ethnicity, comparable to expectations based on the regional demographic characteristics reported by the government (40). Participants were part of a larger study and details about the sample and alcohol consumption were included in previous publications (17, 41). St. Petersburg participants had higher education, higher income, more urban residence, and were employed less often than Nizhny Novgorod Region participants (see Table 1).…”
Section: Resultsmentioning
confidence: 99%